Regulation of Parkin in Cr (VI)-induced mitophagy in chicken hepatocytes - Lumei Wang; Pimiao Zheng; Yukun Cui; Zhuanglong Zhang; Kaimin Song; Yongxia Liu; Jianzhu Liu (Ecotoxicology and Environmental Safety, 2022)
The large amount of heavy metal chromium emissions from industrial production, ore smelting and sewage treatment plants have made chromium one of the most widespread heavy metal pollutants, with Cr (VI) being the most toxic. In recent years, people have gradually recognized the great harm of heavy metal chromium pollution, but the research on its pathogenic mechanism is still not deep enough. In this study, we treated the Primary cells of chicken liver with Cr (VI) to establish a model of toxicity. The optimal treatment time and Cr (VI) concentration were screened using the CCK-8 test. The intracellular mitochondrial membrane potential (MMP) and reactive oxygen species (ROS) were measured qualitatively and quantitatively by laser confocal and flow cytometry, respectively. This result was confirmed by the fact that Cr (VI) could cause mitophagy by causing damage to mitochondria. Subsequently, this study used LMH cells to construct a Parkin silencing model to further investigate that Parkin exerts the function on the Cr (VI)-induced mitophagy in chicken hepatocytes. The results showed that the knockdown of Parkin effectively blocked p62 degradation and LC3 lipidation and that PINK1 expression was significantly inhibited in LMH cells, further suggesting that the knockdown of Parkin effectively inhibited mitophagy. Mitochondrial morphology, MMP, and ROS were observed using laser confocal. The results showed that Parkin knockdown resulted in mitochondrial fission and increased levels of reactive oxygen species, together with increased depolarization of the mitochondrial membrane potential. These changes led to increased mitochondrial damage. In conclusion, this study showed that Cr (VI) could cause the occurrence of mitophagy by damaging mitochondria, and Parkin played a crucial role in Cr (VI)-induced mitophagy in chicken hepatocytes.